Glycemic control in twin pregnancies with gestational diabetes: are we improving or worsening outcomes?. (2nd April 2016) - Fox, Nathan S.; Gerber, Rachel S.; Saltzman, Daniel H.; Gupta, Simi; Fishman, Ariel Y.; Klauser, Chad K.; Rebarber, Andrei
Abstract: Objective : To estimate the association between glycemic control and adverse outcomes in twin pregnancies with gestational diabetes (GDM). Study design : A cohort of patients with twin pregnancies and GDM were identified from one maternal–fetal medicine practice from 2005 to 2014. Patients with prepregnancy diabetes were excluded. First, outcomes were compared between patients with GDMA1 and GDMA2 (gestational age at delivery, birthweight, small for gestational age (SGA, birthweight <10th percentile), preeclampsia, and cesarean delivery). Then, finger stick glucose logs were reviewed and correlated with the risk of SGA and preeclampsia. Abnormal finger stick values were defined as: fasting ≥90 mg/dL, 1-h postprandial ≥140 mg/dL, 2-h postprandial ≥120 mg/dL. Results : Sixty-six patients with twin pregnancies and GDM were identified (incidence 9.1%). Comparing the 43 patients with GDMA1 to the 23 patients with GDMA2, outcomes were similar, aside from patients with GDMA1 having lower birthweight of the smaller twin (2184 ± 519 g versus 2438 ± 428 g, p  = 0.040). The risk of preeclampsia was not associated with glycemic control. Patients with SGA had lower mean fasting values (83.3 ± 5.5 versus 87.2 ± 7.7 mg/dL, p =  0.033), and a lower percentage of abnormal fasting values (24.0% versus 36.9%, p  = 0.040), abnormal post-breakfast values (9.9% versus 27.1%, p  = 0.003), and total abnormal values (20.1% versus 27.7%, p  = 0.055). Conclusion : In twin pregnancies with GDM, improved glycemic control is not associated with improved outcomes, and is associated with a higher risk of SGA. Prospective trials in twin pregnancies should be performed to establish goals for glycemic control in twin pregnancies.